Bidecadal Temperature Anomalies Over the Tibetan Plateau and Arctic in Response to the 1450s Volcanic Eruptions. Issue 5 (25th February 2022) - Liu, Wei; Shi, Feng; Xiao, Guoqiao; Xue, Huihong; Yin, Qiuzhen; Liu, Fei; Duan, Anmin; Xiao, Cunde; Guo, Zhengtang
Abstract: Volcanic eruptions have been the most dominant natural forcing of climate change over the past millennium, affecting temperature change at multiple timescales. However, how volcanic eruptions affect regional temperature variability on the decadal timescale remains unclear. We analyzed the bidecadal effects of volcanic eruptions in the mid‐fifteenth century on two representative regions (the Tibetan plateau [TP] and the Arctic) in the Northern Hemisphere by combining proxy reconstructions, model ensemble simulations, and model sensitive experiments. The results show that the TP experienced bidecadal cooling during the mid‐fifteenth century as a result of the long‐term heat uptake in the midlatitude ocean that reduced latent heat transfer to the atmosphere. A positive sea ice–albedo feedback led to a bidecadal summer temperature decrease in the Arctic comparable to that on the TP, whereas the Arctic winter experienced stronger bidecadal cooling caused by a reduced ocean–atmosphere energy exchange and atmospheric poleward energy transport. In addition, our results show that it took ∼20 years for the temperature in these two regions to return to the level that existed before the first eruption, and this was linked to the strengthening of the Atlantic Meridional Overturning Circulation and ocean heat transport. Plain Language Summary: Simulations and reconstructions covering the past millennia show that a period of prolonged cooling developed during the mid‐fifteenth century, and this was related to the volcanic eruptions in the 1450s. We analyzed the influence of the two volcanic eruptions on Tibetan Plateau (TP) and Arctic temperatures through model–data comparison. Our results show that the inertia of the midlatitude ocean dominated the cooling of the TP, whereas the expansion of sea ice led to the cooling of the Arctic and the adjustment of the atmospheric circulation reinforced the cooling of the Arctic winter. In addition, the ensemble simulations indicate that the response of the Atlantic Meridional Overturning Circulation may have ended the period of cooling caused by the volcanic eruptions in the mid‐fifteenth century. This suggests that volcanic eruptions are an important factor that should be considered in the decadal prediction of regional climate and in geoengineering, especially in representative areas such as the TP and Arctic. Key Points: The Tibetan Plateau and the Arctic experienced bidecadal cooling after two volcanic eruptions in the mid‐fifteenth century The heat uptake of the midlatitude ocean caused bidecadal cooling over the Tibetan Plateau after the volcanic eruptions Reduced sea–air energy exchange and atmospheric poleward energy transport led to the Arctic amplification of winter temperature decrease